Tough Boris - Fox, Mem, 1946-; Brown, Kathryn, 1955- (San Diego : Harcourt Brace Jovanovich, 1994)
Although he is a very tough pirate, Boris von der Borch cries when his parrots dies.
D
b
b
Keywords: Pirates -- Fiction